The Effects of Immigration Enforcement on Faith-Based Organizations: An Analysis of the FEER Survey. (June 2019) - Kerwin, Donald; Nicholson, Mike
Executive Summary: The effects of US immigration enforcement policies on immigrants, US families, and communities have been well documented. Less attention, however, has been paid to their impact on faith-based organizations (FBOs). Faith communities provide a spiritual home, and extensive legal, resettlement, social, health, and educational services, for refugees and immigrants. This report presents the findings of the FEER (Federal Enforcement Effect Research) Survey, which explored the effects of US immigration enforcement policies on immigrant-serving Catholic institutions. 1 Many of these institutions arose in response to the needs of previous generations of immigrants and their children (Kerwin and George 2014, 14, 74–75). Most strongly identify with immigrants and have long served as crucial intermediaries between immigrant communities and the broader society (Campos 2014, 149–51). 2 During its first two years, the Trump administration has consistently characterized immigrants as criminals, security risks, and an economic burden. Among its policy initiatives, the administration has supported major cuts in family-based immigration, attempted to terminate the Deferred Action for Childhood Arrivals (DACA) program, reduced refugee admissions to historic lows, instituted admission bars on Muslim-majority countries, attempted to strip Temporary Protection Status (TPS) from all but a fraction of its beneficiaries, erected major new barriers to asylum, and proposed new rules regarding the public charge grounds of inadmissibility that would make it more difficult for poor and working-class persons to obtain permanent residence. US immigration enforcement policies have separated children from their parents, criminally prosecuted asylum seekers, expanded detention, increased arrests of noncitizens without criminal records, and militarized the US–Mexico border. These policies have failed to stem the flow of migrants and asylum seekers: instead, these flows have increased dramatically in recent months. These policies have succeeded, however, in devastating children, instilling fear in immigrant communities, blocking access to the US asylum system, and undermining immigrant integration (Kerwin 2018). 3 The Federal Enforcement Effect Research (FEER) Survey points to a paradox. On one hand, US enforcement policies have increased the demand for services such as legal screening, representation, naturalization, assistance to unaccompanied minors, and support to the US families of detainees and deportees. Many Catholic institutions have expanded their services to accommodate the increased demand for their services. On the other hand, their work with immigrants has been impeded by federal immigration policies that effectively prevent immigrants from driving, attending gatherings, applying for benefits, and accessing services due to fear that these activities might lead to their deportation or the deportation of a family member. Among other top-line findings, 59 percent of 133 FEER respondents reported that "fear of apprehension or deportation" negatively affected immigrants' access to their services, and 57 percent of 127 respondents reported that immigrant enforcement very negatively or negatively affected the participation of immigrants in their programs and ministries.